(untitled) (MAUSAM, 2001)
A devastating land slide occurred on the early hours of 24 July, 1999 in the hill slopes close to downtown Guwahati. Widespread rain over the NE region and incessant rains over Guwahati area on 23 and 24 July was main reason for the slide which claimed ten (10) human lives almost instantaneously besides damage to property. The various meteorological and geological factors responsible for the land slide have been examined in this study.